Follicular regulatory T cells: a novel target for immunotherapy?. Issue 2 (14th February 2020) - Huang, Yao; Chen, Zhe; Wang, Hui; Ba, Xin; Shen, Pan; Lin, Weiji; Wang, Yu; Qin, Kai; Huang, Ying; Tu, Shenghao
Abstract: High‐affinity antibodies are produced during multiple processes in germinal centres (GCs), where follicular helper T (Tfh) cells interact closely with B cells to support B‐cell survival, differentiation and proliferation. Recent studies have revealed that a specialised subset of regulatory T cells, follicular regulatory T (Tfr) cells, especially fine‐tune Tfh cells and GC B cells, ultimately regulating GC reactions. Alterations in frequencies or function of Tfr cells may result in multiple autoantibody‐mediated or autoantibody‐associated diseases. This review discusses recent insights into the physiology and pathology of Tfr cells, with a special emphasis on their potential roles in human diseases. Discrepancies are common among studies, reflecting the limited understanding of Tfr cells. Further exploration of the mechanisms of Tfr cells in these diseases and thus targeting Tfr cells may help reinstate immune homeostasis and provide novel immunotherapy. Abstract : This review discusses the physiology and pathology of follicular regulatory T (Tfr) cells, which remains largely unknown. Numerical and functional alterations of Tfr cells are observed in a multitude of diseases, predominantly in autoimmune diseases. Better methods to obtain bona fide Tfr cells in humans and more precise designation for Tfr cells are required to assess their underlying mechanisms, ultimately developing novel immunotherapy.